Macramé for home décor : 40 stunning projects for stylish decorating - Grenier, Samantha (Fox Chapel Publishing, 2019)
The art of macramé has steadily been making a comeback! This textile art of designing with knots traces back thousands of years, but now it is the hip new trend among millennial crafters. In Macramé for Home Décor, you'll discover the 12 essential knots you need to create gorgeous macramé. 40 stylish projects range in skill level from easy to advanced, so there's something here for everyone! This book is filled with cool, contemporary, creative ideas for using natural macramé craft cords for chic rugs, throws, coverlets, room dividers, boho plant hangers, chair backs, pillow coverings, wall art, and much more. Mixed-media projects are also included that incorporate fun and interesting materials like beads and rings. The step-by-step illustrations, clear instructions, and beautiful color photographs inside Macramé for Home Décor make macramé simple and fun!